Teachers' self-efficacy in teaching family life education - Jamaluddin, Rahimah; Abu, Rosini; Ismail, Habsah; Mat Rashid, Abdullah (Universiti Putra Malaysia Press, 2014)
Although the notion of self-efficacy has been applied to many domains, little is known regarding teacher efficacy in teaching family life. Self-efficacy in this study refers to teachers' beliefs that their efforts can improve students' moral characters and behaviors in relation to family life. In Malaysian secondary schools, aspects of family life are taught through five different subjects. Therefore, there is a need for studying teachers' self-efficacy in teaching family life, which is the main purpose of this research. In this research, the Teachers' Sense of Efficacy Scale, developed by Tschannen-Moran and Woolfolk Hoy (2001), was used to measure teachers' self-efficacy. Data was collected from 419 secondary school teachers who teach family life. Findings indicated that respondents had moderate self-efficacy for the overall teaching efficacy as well as three sub dimensions of efficacy. The implication of the study is discussed in the last part of the paper. Suggestions offered are hopefully to be considered to enhance and foster teacher efficacy in teaching family life.